KAJIAN CONSPIRACY THEORY PADA KEPALA DAERAH MELALUI INSTRUMEN PBB-P2 DI KABUPATEN/KOTA DI JAWA TIMUR - Rachmad Kresna Sakti (EP FEB UNS, 2020)
The delegation of authority to manage the Land and Building Tax on Rural and Urban (PBB-P2) from the provincial government to the district / city government provides an opportunity for the district / city government to get additional Regional Original Revenue (PAD). But the fact that what happens is that the PAD revenues are sourced from UN-specific taxes which experience abnormal fluctuations. This is indicated by the interests of regional heads who want to maintain the stability of their territory through populist policies. To look deeper into this matter, the qualitative method is used by utilizing the literature study approach as an approach in completing this study. The findings obtained are proven to be a link between the increase in the UN-P2 revenue target and the periodization of regional heads (regents / mayors) in which the regional head who nominates again as regional head for the second period will loosen policy towards PBB-P2. But when it has been chosen definitively, the policy against PBB-P2 will return to strict. However, this connection cannot occur in the regions (regencies and / or cities) under certain conditions Keywords: Tax Policy, Land and Building Tax in Rural and Urban Areas (PBB-P2), Periodization of Regional Head.